Review of the Poecilimon (Poecilimon) zonatus species group and description of new species from Turkey with data on bioacoustics and morphology (Orthoptera: Phaneropterinae) - Sevgi̇li̇, Hasan; Şi̇ri̇n, Deni̇z; Heller, Klaus-Gerhard; Lemonnier-Darcemont, Mi̇chèle (Zootaxa, 2018)
The aim of this study is to conduct a detailed taxonomic revision of the Poecilimon (Poecilimon) zonatus species-group (Orthoptera: Phaneropterinae) using both morphology and bioacoustics. Two new species (Poecilimon (Poecilimon) salmani, P. (P) azizsancar) and one new subspecies (P. (P) zonatus datca) are described. Based on the data, we conclude that the species complex can be separated into two subgroups (P. tauricola and P. zonatus). Within the P. zonatus subgroup, song structures indicate P. variicercis as basal branch since producing two syllable types is possibly a derived character. From both, from bioacoustics and morphology, it is concluded that the relationships between species of the group are as follows: P. tauricola subgroup (P. tauricola + P. azizsancar) + P. zonatus subgroup (P. variicercis + (P. varicornis + (P. zonatus zonatus+P. zonatus datca)) + (P. salmani+P. vodnensis)))). Except for two species (P. vodnensis and P. varicornis), the other species of the group are all distributed in Anatolia. P. vodnensis is known only from Macedonia, whereas, P. varicornis has been recorded only from Syria and Lebanon. We assume that the group originated from an Anatolian ancestral stock and expanded its distribution to the Balkans through Taurus Way and Dardanelles. Other ancestral populations may have also spread in the north-south directions through the appropriate steppe corridors in the Anatolian Diagonal Mountains and in its vicinity.